Quality Control of The Miftahul Huda Mosque Social Program, Balun Village, Turi District, Lamongan Regency - Fahny Rizal; Ah. Ali Arifin (Proceedings of International Conference on Da'wa and Communication, 2020)
This study aims to determine how the process of controlling the quality of the social program of the Miftahul Huda Mosque, Balun Village, Turi District, Lamongan Regency. This research uses descriptive qualitative research method. Qualitative descriptive method is used to describe and examine in depth the process of quality control of the social program of the Miftahul Huda Mosque, Balun Village, Turi District, Lamongan Regency. Then, the data collection technique was carried out by means of interviews, observation, and documentation. The results of this study are as follows. Miftahul Huda Mosque's social programs include providing death compensation (adults Rp. 400,000/person, children Rp. 300,000/person, providing coffins), anjangsana to sick families, assistance to families affected by natural disasters, and providing compensation. to orphans and less fortunate people twice (just before Eid al-Fitr and at PHBI Maulid Prophet Muhammad SAW). Miftahul Huda Mosque makes efforts to control the quality of social programs by going through several processes, namely program planning, implementation monitoring, quality assurance, quality improvement, program innovation, standardization of activities, persuasive efforts, reporting systems, and evaluation.